Prosedur Penanganan Bongkar Muat Muatan Berbahaya Melalui Sistem Inaportnet Oleh PT. Seroja Jaya Agensi Cabang Kuala Tanjung - Prima Ananta Ginting; Suratni Ginting; Meriah Kita Deliani (Pusat Riset dan Inovasi Nasional, 2025)
The loading and unloading process of dangerous goods at ports requires selective operational standards to ensure safety, security, and smooth logistics flow. The Inaportnet system as an integrated digital platform in port services has been implemented to accelerate and simplify the administrative process of cargo handling, including dangerous goods. This research aims to examine the procedures for handling dangerous goods through the Inaportnet system, analyze the effectiveness of its implementation, and identify challenges and solutions encountered in the field. The research methodology employs field observation and library research. Based on Minister of Transportation Regulation PM 16 of 2021, dangerous goods are classified into three forms: liquid, solid, and gas, with nine hazard classes according to IMDG Code. Handling procedures include cargo classification, labeling and packaging according to standards, and permit processing through Inaportnet which encompasses system login, BMBB application creation, document verification, KSOP approval, and PNBP payment. This system integrates data among agencies such as KSOP, Customs, KPLP, and Pelindo for real-time monitoring, enhancing transparency and port operational efficiency. Research findings indicate that Inaportnet provides convenience in licensing and monitoring dangerous goods. However, obstacles encountered include technical server disruptions, document delays from third parties, and limited supporting facilities at several wharves. Recommended solutions include strengthening technology infrastructure, implementing emergency manual protocols, enhancing HR competency, expanding port facilities, and improving inter-agency integration to optimize the system in supporting maritime safety and national logistics efficiency.